2006
DOI: 10.1002/ps.1266
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal, antifeedant and oviposition deterrent effects of the essential oil and individual compounds from leaves of Chloroxylon swietenia DC.

Abstract: Essential oil from the leaves of Chloroxylon swietenia DC. was obtained by hydrodistillation and cold extraction, and the chemical composition was determined by gas chromatography and gas chromatography-mass spectrometry. The major identified components were limonene, geijerene, pregeijerene, germacrene D and trans-beta-ocimene. Laboratory bioassays of the essential oil and four constituents of essential oil isolates were evaluated for insecticidal, antifeedant and oviposition deterrent effects on tobacco cutw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…lithophila oil [18] and we were the first to show the occurrence of traginone and dictamnol in Pimpinella. Kiran et al recently reported that geijerene and pregeijerene displayed oviposition deterrence effects on the tobacco cutworm, Spodoptera litura, at low concentration [36]. The quantity of geijerene and pregeijerene present make S. tripartita a good source of these compounds as potential natural pesticides.…”
Section: Resultsmentioning
confidence: 98%
“…lithophila oil [18] and we were the first to show the occurrence of traginone and dictamnol in Pimpinella. Kiran et al recently reported that geijerene and pregeijerene displayed oviposition deterrence effects on the tobacco cutworm, Spodoptera litura, at low concentration [36]. The quantity of geijerene and pregeijerene present make S. tripartita a good source of these compounds as potential natural pesticides.…”
Section: Resultsmentioning
confidence: 98%
“…Our results also suggest that 'geijerenes' mediate this response. These C 12 terpenes have not been described for citrus previously; however, they are known for insecticidal, antifeedant, and oviposition deterrent effects in leaves of other rutaceous plant species (Kiran et al 2006;Kiran and Devi 2007). Geijerenes also have been described in hairy root cultures of Pimpinella anisum (Santos et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…This difference could of course be due to other different physiological/biochemical characteristics. 11) Essential oils have been utilized as insecticides, antifeedants, and repellents with a wide variety of target insects [12][13][14][15][16][17][18][19][23][24][25][26][27] ; however, one study that tested 96 herb extracts found that while Japanese mint oil had a strong repellent effect against B. germanica, the essential oils of grapefruit, lemon, and lime did not show strong repellent activity. 28) This is in contrast with our results, but the previous study was performed by a classical assay method based on the behavior of cockroach groups, and this may have been affected by the chemical factors associated with aggregation.…”
Section: Repellency Of Essential Oilsmentioning
confidence: 99%